Enhancement of Solubility and Dissolution Rate of Atazanavir Sulfate by Nanocrystallization - Malviya, Vedanshu; Burange, Prashant; Thakur, Yashdeepsingh; Tawar, Mukund (Indian Journal of Pharmaceutical Education and Research, 2021)
Objectives: The current objective of the present study was to enhance the solubility and dissolution rate of the antiviral drug atazanavir sulphate by employing nanocrystallization technique. Materials and Methods: The method employed for increment of solubility was nanocrystallization which is based on the reduction of particle size of the drug thereby increasing its solubility and also its dissolution property. Various polymers in different ratios were used like HPMC K15M, PVP K30 and PEG 6000. Results: Drug and polymers were firstly tested for their interaction between each other’s and it was found that the drug and polymers are compatible with each other. From the solubility study it was seen that the solubility of the optimized batch was increased to 40.068mg/ml in distilled water and 160.182mg/ml in phosphate buffer while the pure drug shows the solubility of 4.174mg/ml in distilled water and 20.547mg/ml in phosphate buffer. The percent drug release of the optimized formulation was seen of 87.91% in 2 hrs which was maximum from all the other batches. The stability study revealed that the prepared nanocrystal does not show any insignificant changes and therefore it can be concluded as stable. Conclusion: The prepared nanocrystals are the proof that this method of nanocrystallization may prove to be an efficient method in increasing the solubility and dissolution rate of the drug which are having low solubility and low bioavailability.
Keywords: Atazanavir Sulphate; Nanocrystallization; Solubility Enhancement; Dissolution Enhancement; Antiviral